Mendapatkan profil suhu serta kelembapan di PTAR, ITM, Shah Alam / Azhar Shukor - Shukor, Azhar (1987)
The purpose of this project is to get the temperature and the humidity profile for the main, library of ITM Shah Alam. The main aim of this project is to minimize the electrical consumption of the air conditioning plant and also to determine the electrical consumption. In this report, discussion was made on how to minimize the energy consumed by the air-cond plant, what should be done and etc.